The Effect of Ratio of Jackfruit Seed and Water and Carboxy Methyl Cellulose Concentration on the Quality of jackfruit seed extract yogurt - Sri Marlena Ketaren; Herla Rusmarilin; Setyohadi . (Universitas Sumatera Utara, 2013)
The research was conducted on April to Mei 2012 in the Laboratory of Food Technology, Faculty of Agriculture,University of Sumatera Utara, Medan, using factorial completely randomised used design with ratio of jackfruit seed andwater (1:1, 1:2, 1:3, and 1:4) and carboxy methyl cellulose concentration (0,1%; 0,2%; 0,3%, and 0,4%). Parametersanalysed were total solid content, protein content, total lactid acid content, pH, total microbe, organoleptic value offlavour, taste, and texture. The results indicated that the ratio of jackfruit seed and water and carboxy methyl celluloseconcentration had highly significant effect on total solid content, protein content, total lactid acid content, pH, totalmicrobe, organoleptic value of taste and texture, and had significant effect on organoleptic value of flavor.